2022
DOI: 10.1039/d2cc03921d
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-promotedS-trifluoromethylation of thiophenols with trifluoromethyl phenyl sulfone

Abstract: Trifluoromethyl phenyl sulfone is traditionally a nucleophilic trifluoromethylating agent. Herein, we report the first example of the use of trifluoromethyl phenyl sulfone as a trifluoromethyl radical precursor. Arylthiolate anions can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…6 The research group of Hu et al described a photochemical trifluoromethylation reaction in which an electron donor–acceptor complex between an aromatic thiophenolate anion and trifluoromethylphenylsulfone initiates a single electron transfer, and therefore the generation of CF 3 radicals. 7 In other photocatalytic trifluoromethylations of aromatics CF 3 SO 2 Na 8 or trifluoromethanesulfonic anhydride 9 were used as trifluoromethyl radical source. Note also that in 2009 MacMillan et al reported on an enantioselective trifluoromethylation of aldehydes via a photoredox process coupled with organocatalysis on using the Ir redox catalyst [Ir(dtbbpy)(ppy) 2 ]PF 6 (4,4′-di- tert -butyl-2,2′-dipyridyl, ppy = 2-phenylpyridine).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The research group of Hu et al described a photochemical trifluoromethylation reaction in which an electron donor–acceptor complex between an aromatic thiophenolate anion and trifluoromethylphenylsulfone initiates a single electron transfer, and therefore the generation of CF 3 radicals. 7 In other photocatalytic trifluoromethylations of aromatics CF 3 SO 2 Na 8 or trifluoromethanesulfonic anhydride 9 were used as trifluoromethyl radical source. Note also that in 2009 MacMillan et al reported on an enantioselective trifluoromethylation of aldehydes via a photoredox process coupled with organocatalysis on using the Ir redox catalyst [Ir(dtbbpy)(ppy) 2 ]PF 6 (4,4′-di- tert -butyl-2,2′-dipyridyl, ppy = 2-phenylpyridine).…”
mentioning
confidence: 99%
“…However, under the UV irradiation SF 4 might also be further reduced yielding elemental sulfur, as it was also proposed by Nagorny et al for the activation of SF 6 in the presence of the organophotocatalyst 4,4-dimethoxybenzophenone. 15 Indeed, when PPh 3 was added to the reaction mixture after the photolytic formation of C 6 D 5 CF 3 , the generation of small amounts of SPPh 3 (7) was observed after heating the reaction mixture for two hours at 60 1C, which might be due to the presence of sulfur (Scheme 4).…”
mentioning
confidence: 99%
“…[33] Hu and co-workers described the photochemical S-trifluoromethylation of thiophenols 7.1 that occurred in moderate to good yields under both metal and (photo)catalyst free conditions (Scheme 7). [34] The key step is the formation of a colored EDA complex between an in situ generated thiolate anion and the electron poor trifluoromethyl phenyl sulfone 7.2 employed as the trifluoromethyltiolating agent. In some cases, the use of trifluoromethyl 4-trifluorophenyl sulfone was required to improve the reaction yield.…”
Section: Thiols As Thiolating Agentsmentioning
confidence: 99%
“…Molander and co-workers established the photoinduced site-selective CÀ H thioetherification of thianthrenium salts 10.1 by aromatic thiols 10.2 in the presence of an inorganic base, to provide a wide range of thioethers 10.3 in up to excellent yields (Scheme 10). [39] The EDA complex formed between the electronacceptor thianthrenium salts and electron-donor thiolate anion acts as both visible light absorbing and photoreactive species.…”
Section: Thiols As Thiolating Agentsmentioning
confidence: 99%
See 1 more Smart Citation